SAR interferometry analysis from 2015 Mw 6.0 earthquake in Ranau, Sabah using Alos Palsar-2 data - Abd Razak, Janatul Aziera; Rambat, Shuib; Mohamed Shariff, Abdul Rashid (2018)
The 2015 Sabah earthquake on June 5 at Mw 6.0 suggests that the faulty lines around the tectonic landform in the region is active and, in future, the seismically active plate is capable of generating an even greater earthquake in terms of its magnitude or intensity scale. Thus, the main purpose of this study is to clarify the changes in the tectonic landform due to the ground displacement that occurred from the 10 km depth-earthquake with the strong evidence from the aftershocks within the seismic activity zone whereby geological hazard such as mud-flood becoming more frequent. Two scenes from Alos Palsar-2, level 1.1 datasets acquired on January 19, 2015 and June 22, 2015 were used to extract the deformation patterns cause by the earthquake. A notable coherence distribution pattern was detected from an image generated via interferometric SAR (InSAR) analysis of the pre and post-earthquake SAR images which has been used for measuring a coherent deformation field in the study area.